Bridging the gap in healthcare: creating an online health information prototype for individuals with intellectual disabilities to promote equity and knowledge transfer - Lisa T. Dam; Petra Heidler; Petra Heidler; Isabel King (Frontiers Media S.A., 2023)
IntroductionThe prevalence of intellectual disabilities (ID) in Austria is estimated to be approximately 1% of the population. Growing awareness of the major challenges faced by individuals with ID, including difficulties in comprehending written health information, communication barriers with healthcare professionals, and limited inclusion in health education research, necessitates concerted efforts to address these issues. The utilization of guidelines promoting easy-to-read language, web accessibility, and usability can significantly enhance access to health information and improve health literacy among people with ID. The "LUCHS-Gesundheitsinformationen (Health Information)" project aimed to improve knowledge transfer of health information for people ID by creating a website prototype.MethodsUnstructured interviews were conducted with two focus groups (n = 20) people with ID and their caretakers to elicit relevant topics and ensure the quality, comprehensibility, and usability of a website prototype. A convenience sample of 20 adults employed in sheltered workshops of the Caritas Lower Austria West facility who met the inclusion criteria participated.ResultsThe prototype addressed four main topics, namely nutrition, medical specialization, first aid, and patient information, offering comprehensive information using easy-to-read language and pictorial content. The website prototype followed web accessibility suggestions and incorporated external resources, such as brochures and emergency contact details, to enhance usability and provide a reliable source of health information for individuals with ID.DiscussionThe findings suggest that a website format is a feasible means of providing accessible online health information for people with ID. However, further research is warranted to explore the potential of digital health applications for individuals with ID, as inclusion in the Austrian register for digital health applications necessitates meeting multiple quality standards, thereby instilling trust among the target group.